2009
DOI: 10.1016/j.jag.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing optical earth observation systems for mapping and monitoring temporary ponds in arid areas

Abstract: Remote sensing methods for locating and monitoring temporary ponds over large areas in arid lands were tested on a study site in Northern Senegal. Three main results are presented, validated with field data and intended to highlight different spectral, spatial and temporal characteristics of the methods: (1) Among several water indices tested, two Middle Infrared-based indices (MNDWIModified Normalized Difference Water Index and NDWI1Normalized Difference Water Index) are found to be most efficient; (2) an obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 17 publications
4
67
0
Order By: Relevance
“…Generally, the limits of these ponds are delineated by a belt of trees which corresponds to the maximum water extension. Most of the ponds in the study area are small (33% of ponds with an area less than 1000 m 2 and 64% with less than 2600 m 2 ), with the smallest one covering only 74 m 2 and the largest one, Barkedji, covering ∼347 400 m 2 (Soti et al, 2009). The larger ponds are located in the main stream of the Ferlo valley and the smaller ones generally outside.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, the limits of these ponds are delineated by a belt of trees which corresponds to the maximum water extension. Most of the ponds in the study area are small (33% of ponds with an area less than 1000 m 2 and 64% with less than 2600 m 2 ), with the smallest one covering only 74 m 2 and the largest one, Barkedji, covering ∼347 400 m 2 (Soti et al, 2009). The larger ponds are located in the main stream of the Ferlo valley and the smaller ones generally outside.…”
Section: Study Areamentioning
confidence: 99%
“…In arid areas, the potential of time series from coarse-scale satellites images like NOAA-AVHRR (Verdin, 1996), SPOT-Vegetation (Haas et al, 2006) or Terra-MODIS (Moderate Resolution Imaging Spectroradiometer) to survey large ponds and lakes at a broad spatial scale was demonstrated. Nevertheless, in the Sahel region, the spatial resolution of those sensors is inappropriate (Soti et al, 2009) for identifying water bodies with a surface area of less than 170 000 m 2 (Soti et al, 2009), which is the case for most of the ponds there. Recently, it was shown that the new generation of high and very high spatial resolution remote sensing data (Landsat Enhanced Thematic Mapper, SPOT5 and Quickbird images) is suitable for the detailed mapping of temporary water bodies at a local scale (Liebe et al, 2005;Lacaux et al, 2007;Soti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…vegetation or water, to enhance classification results. Based on information gathered from other studies on water bodies (Lillesand et al, 2004;Soti et al, 2009Soti et al, , 2010Wolf, 2010), the following indices were created and explored in view of SWB delineation: the normalised difference water index (NDWI) = (coastal blue -NIR2) / (coastal blue + NIR2), the standing water index (SWI) = (blue -NIR1)/(blue + NIR1) and the normalized difference vegetation index (NDVI) = (NIR1 -red) / NIR1 + red). These indices, together with the hue (red, green, blue) transformation, were incorporated in the analysis.…”
Section: Indices and Ratiosmentioning
confidence: 99%
“…spatial resolution of <5 m, has made it possible to acquire spatial accuracy at sub-meter scales thereby allowing the detection of water bodies that cover only a few m 2 . However, few initiatives have been undertaken to monitor SWBs using VHR satellite imagery (Dambach et al, 2009;Soti et al, 2009;Soti et al, 2010). Many studies use the freely available Landsat imagery (about 30-m resolution) and medium (20 m to 100 m) or coarse (>100 m) resolution imagery (Fuentes et al, 2001;Malone et al, 2001;Guo et al, 2005;Daniel et al, 2006;de Castro et al, 2006;Estallo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%